The role of p97 cofactors SPRTN and FAF1 in DNA replication - Halder, S (2016)
It is well known that cancer cells are loaded with excess proteins. To survive this proteotoxic crisis cancer cells rely heavily on the ubiquitin proteasome system (UPS). Valosin containing protein (VCP) or p97 has recently emerged as a central player of UPS. Moreover, p97 inhibitors were shown to possess potent anti-cancer properties. Owing to the essential function of p97, it can be assumed that general p97 inhibition will be equally toxic to surrounding normal tissues. Interestingly, p97 employs diverse sets of cofactors to govern distinct biological pathways. Thus understanding the p97-cofactor interaction in specific pathways may give us the ultimate edge by allowing us to abolish those cancer specific p97-cofactor interactions in our fight against cancer. This thesis explains novel function of two bonafide p97 cofactors SPRTN and FAF1 in DNA replication. Our discovery of a new human syndrome followed by its characterisation that monogenic and biallelic mutations in SPRTN leads to premature aging and juvenile hepatocellular carcinoma, have led us to identify the critical function of SPRTN in DNA replication. Our follow up work further revealed that SPRTN is a novel protease in humans and has the essential function in covalent DNA-protein crosslinks (DPCs) repair. To this end, we have found that SPRTN proteolytically removes CHK1 from chromatin, which is evolutionary conserved and vital for replication fork progression to preserve genomic integrity. Additionally, this thesis also explains a novel mechanism through which FAF1 downregulation in cancer cells might promote genomic instability. Our data supports a model where the p97-FAF1 complex binds to ubiquitinated CDT1 and degrades it via the proteasome after CDT1 mediated replication initiation, to prevent re-replication and genomic instability. The notion that high replication stress in some cancers can be utilised as an Achilles heel, led to the search for novel factors involved in DNA replication owing to its high therapeutic potential. Replication factors with enzymatic activities are especially appealing due to the relative ease of targeting them by small molecule inhibitors. This thesis thus highlights the great potential of the p97 systems in our battle against cancer.